Use of library information technology services in Perpustakaan Sultan Abdul Samad, UPM: users' perceptions - Samsuddin, Samsul Farid; Mat, Shaifol Yazam (2011)
Information and technology (IT) services is the main element of the quick-access of information provided by Perpustakaan Sultan Abdul Samad (PSAS). It plays a very significant role in PSAS and is geared towards fulfilling the information needs of users in learning, teaching, research and consultation. The aim of this study is to obtain users' perception of IT services in PSAS. The analysis includes the estimation of the relative importance and the level of users' satisfaction of the services provided. This information can be used to improve the quality of IT service given by the library. The study covers seven (7) main elements of IT services in PSAS: the Website, Online Public Access Catalog (OPAC), Online Databases (Online Journals, E-Book, CD-ROM and Index/Abstract), Internet Services, Self-Check Machines, Book Drop and Wifi services. The importance and the satisfaction of the services are the two variable that have been measured in this study using Likert Scale. Frequencies and means analysis are used to measure the data. A total of 381 questionnaires have been received out of 500 which were distributed to identify respondents within the population. The study was also used to identify the usage trend of the IT services provided by PSAS.